Designing a Hypothetical Learning Trajectory Based on Investigative Learning - Charina Ulfa; Ariyadi Wijaya; Habibullah Habibullah (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2021)
This research is a design research that aims to design a hypothetical learning trajectory based on investigative learning. This studyâ€™s subjects were students of class VII in a junior high school in Aceh Barat Daya, consisting of 32 students for the pilot experiment and 31 students for the teaching experiment. The selection of research subjects for these two classes used a random sampling technique. The data collection technique were carried out by observation, interview, and documentation. The research data were analyzed using qualitative analysis. This design research model consists of three stages: preparing for the experiment, experimental design, and retrospective analysis. The results showed that the hypothetical learning trajectory based on group investigative learning that has been designed can help students achieve learning goals. The learning trajectories produced in this study are (1) students can find the size of the object on the two sketchs by measuring and making comparisons of the two sketchs object values (the same amount); (2) students can find the form of the ratio from the size of the two sketchs and students can draw the conclusion that from the ratio value can be obtained the scale value; (3) students can determine the ratio of two different quantities of the investigative activity carried out and can write a form of direct proportion; and (4) students can distinguish the form of direct proportion and inverse proportion problemsÂ